Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations Health and Cleanliness A Textbook for Teachers BY W.A. MUIR M.D., D.P.H. Medical Officer of Health for Gillingham, Kent AND GEORGE H. GREEN Ph.D., B.Litt. (Oxon), B.Sc. (Lond.), M.A.. M.R.S.T. Lecturer in Education, University College of Wales, Author of "Psychanalysis in the Class Room" and "The Day Dream" WITH FOREWORDS BY G.F. BUCHAN, M.D., F.R.C.P., D.P.H. Medical Officer of Health for Willesden, President of the Health and Cleanliness Council [Logo] Where there's dirt There's danger PUBLISHED BY THE HEALTH AND CLEANLINESS COUNCIL 5, TAVISTOCK SQUARE, LONDON, W.C.1 B5 177/5/8/3